VERY LOW BIRTH WEIGHT BABIES WITH NECROTIZING ENTEROCOLITIS - INCIDENCE AND OUTCOME - Syed Sajid Hussain Shah; Tahir Mahmood (Journal of University Medical & Dental College, 2016)
Abstract: Background:Necrotizingenterocolitis (NEC) is the one of the commonest gastrointestinalemergency and leadingcause of mortality in preterm and very low birth babies (VLBW). Objective: This study was conducted to determine the incidence and outcome of necrotizing enterocolitis in very low birth weight babies during stay in hospital. Design: Case series Methods: This was descriptive case series carried out in neonatal Intensive Care Unit (NICU) of child health department, Pakistan Ordnance Factories (POF) Hospital, Wah Cantt from August 2010 to February 2011. All very low birth babies having weight < 1500 grams admitted under 28 days of age in NICU of POF Hospital were included in the study. Patients were clerked on a pre-designed proforma. Results: Out of selected fifty six very low birth babies, about fifteen patients developed NEC which is about 26.8% with mortality of 53.33% in patients having NEC as outcome. Conclusion: The frequency of NEC in this study was 26.8% which is too high in very low birth weight babies. NEC is associated with complications like neurodevelopment delay and death, so timely diagnosis and management of NEC should be done.